Ciliogenesis is reciprocally regulated by PPARA and NR1H4/FXR through controlling autophagy in vitro and in vivo. Issue 6 (3rd June 2018) - Liu, Zhi-qiang; Lee, Joon No; Son, Myeongjoo; Lim, Jae-Young; Dutta, Raghbendra Kumar; Maharjan, Yunash; Kwak, SeongAe; Oh, Goo Taeg; Byun, Kyunghee; Choe, Seong-Kyu; Park, Raekil
ABSTRACT: The primary cilia are evolutionarily conserved microtubule-based cellular organelles that perceive metabolic status and thus link the sensory system to cellular signaling pathways. Therefore, ciliogenesis is thought to be tightly linked to autophagy, which is also regulated by nutrient-sensing transcription factors, such as PPARA (peroxisome proliferator activated receptor alpha) and NR1H4/FXR (nuclear receptor subfamily 1, group H, member 4). However, the relationship between these factors and ciliogenesis has not been clearly demonstrated. Here, we present direct evidence for the involvement of macroautophagic/autophagic regulators in controlling ciliogenesis. We showed that activation of PPARA facilitated ciliogenesis independently of cellular nutritional states. Importantly, PPARA-induced ciliogenesis was mediated by controlling autophagy, since either pharmacological or genetic inactivation of autophagy significantly repressed ciliogenesis. Moreover, we showed that pharmacological activator of autophagy, rapamycin, recovered repressed ciliogenesis in ppara − /− cells. Conversely, activation of NR1H4 repressed cilia formation, while knockdown of NR1H4 enhanced ciliogenesis by inducing autophagy. The reciprocal activities of PPARA and NR1H4 in regulating ciliogenesis were highlighted in a condition where de-repressed ciliogenesis by NR1H4 knockdown was further enhanced by PPARA activation. The in vivo roles of PPARA and NR1H4 in regulating ciliogenesis were examined in greater detail in ppara − / − mice. In response to starvation, ciliogenesis was facilitated in wild-type mice via enhanced autophagy in kidney, while ppara − / − mice displayed impaired autophagy and kidney damage resembling ciliopathy. Furthermore, an NR1H4 agonist exacerbated kidney damage associated with starvation in ppara − / − mice. These findings indicate a previously unknown role for PPARA and NR1H4 in regulating the autophagy-ciliogenesis axis in vivo.